2017
DOI: 10.1016/j.ypmed.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

“Can we walk?” Environmental supports for physical activity in India

Abstract: India is currently facing a non-communicable disease epidemic. Physical activity (PA) is a preventative factor for non-communicable diseases. Understanding the role of the built environment (BE) to facilitate or constrain PA is essential for public health interventions to increase population PA. The objective of this study was to understand BEs associations with PA occurring in two major life domains or life areas-travel and leisure-in urban India. Between December 2014 and April 2015, in-person surveys were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 86 publications
(108 reference statements)
1
43
1
Order By: Relevance
“…In high-SES populations in India, the dependence on the automobile is apparent as ordinary, everyday tasks such as a trip to the corner store, coffee shop, getting to school or work that used to be completed on foot, are now accomplished by driving to those destinations in privately owned cars. 76,100 The availability of new technologies and electronic devices (e.g., televisions, computers, electronic entertainment, the internet, and wireless communication devices) has enabled people to reduce the amount of physical labor needed to accomplish many tasks in their daily lives. 6 The pervasive nature of technology, proliferation of new devices, and the transition from the traditional physically demanding agricultural and industrial employment to mechanized manufacturing processes has altered patterns of movement and energy expenditure at home, work, during leisure, and travel in India.…”
Section: Discussionmentioning
confidence: 99%
“…In high-SES populations in India, the dependence on the automobile is apparent as ordinary, everyday tasks such as a trip to the corner store, coffee shop, getting to school or work that used to be completed on foot, are now accomplished by driving to those destinations in privately owned cars. 76,100 The availability of new technologies and electronic devices (e.g., televisions, computers, electronic entertainment, the internet, and wireless communication devices) has enabled people to reduce the amount of physical labor needed to accomplish many tasks in their daily lives. 6 The pervasive nature of technology, proliferation of new devices, and the transition from the traditional physically demanding agricultural and industrial employment to mechanized manufacturing processes has altered patterns of movement and energy expenditure at home, work, during leisure, and travel in India.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study from Chomitz’ et al [48] linked the cultural context of India that assigns women to household chores to their reportedly low PA. In their study of the association between built environment (BE) and PA, Adlakha et al [49] supported the notion that the understanding of PA is limited to three categories of work, leisure and travel, which ignores the household work of people in slums. Manjrekar et al [50] linked the lower PA of women in slums to a higher risk of developing NCDs in their comparative study between working and non-working women in urban India.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, they urged for greater collaboration between government agencies to deal with changing patterns in urban transportation. Adlakha et al [49] examined the connection between BE and PA in Chennai, India, distributing the International Physical Activity and Environment Network (IPEN) survey questionnaire to 292 participants from four different SES. They concluded that people with a lower SES obtain their PA from travel (walking and biking), while people with a higher SES obtain their PA from leisure.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these benefits, mass adoption of private motorised transport and the design of cities to favour automobile use has likely resulted in declining levels of active commuting and a rise in population prevalence of overweight, obesity, and related NCDs in India [14]. Our previous research from India showed that urban living was associated with lower leisure-time and transport physical activity and increasingly sedentary lifestyles [15,16]. Active commuting may be influenced by characteristics of the neighbourhood built environments, yet few studies have quantified the associations between these factors in India.…”
Section: Introductionmentioning
confidence: 99%
“…These countries have implemented effective policies and made investments in urban environments to increase active commuting. However, such efforts remain largely under-developed in LMICs like India, which suffers from fundamental concerns such as overcrowded street conditions, lack of activity-supportive infrastructure, and poor enforcement of traffic rules and regulations, all of which create barriers to active commuting [16,18].…”
Section: Introductionmentioning
confidence: 99%